Effets du coenseignement sur le développement de l’identité professionnelle des enseignants du secondaire - Nancy Granger; Philippe Tremblay (Éducation et Socialisation)
Co-teaching is one of the most widely used service models for supporting the education of special needs students in the regular classroom. It offers a favourable context for teachers who wish to improve their pedagogical and collaborative practices. However, this collaboration is not easy to achieve and generates role tensions. The objective of this case study conducted with two pairs of female co-teachers at the lower secondary level is to identify these tensions and, more specifically, to understand their influence on the development of their professional identity. The results show that issues of negotiation, action and reflection are at the root of professional identity development. The co-teachers of the two pairs evolved, following the same process (negotiation - action - reflection) but in different ways according to the context, the issues, the identity of each one, among others.